Neoliberal resilience lessons in democracy and development from Latin America and Eastern Europe - Madariaga, Aldo (Book collections on Project MUSE., 2020)
"An exploration of the factors behind neoliberalism's resilience in developing economies and what this could mean for democracy's future"--